Evaluation of techniques to reduce the concentration of sedimentable solids in the wastewater produced in the coal mining in the municipality of Guachetá, Cundinamarca (2021)
Eng: The filtration of surface and groundwater is very common when mining works is advancing, since underground aquifers, old blocks exploited must be crossed and within the extraction process, a settlement of the strata that produce some range of subsidence and fracture of these is generated, resulting in the filtration of these waters from the surface of the ground to inside of the mines. This wastewater must be evacuated back to the surface, which it is necessary to conduct it throughoutthe mining works (using mechanisms such as ditches, hoses and pipes), tending to contaminate with the environment of mining pollution and the same direct contact with the rocks of the excavations. Once driven to the surface, by means of pumps of great capacity and flow depending on the depth of the work, these wastewaters must be managed in treatment systems in order to perform a cleaning in this case of the concentrations of sediment solids and be able to be discharged to nearby sources, to be reused in processes other than human consumption. The present study evaluated in a technical,economic and environmental way three water treatment alternatives, getting results from alternative 1 Coagulation-Flocculation, an efficiency percentage of 99.12%, a total installation cost of $17,363,978 Colombian money, and a low environmental affectation, simulating with the SuperDecisions® software, that Alternative 1 Coagulation-Flocculation has the ranking number 1, followed by the alternative Activated Carbon with ranking number 2 and, finally the maintenance of the system with ranking 3.